SMAC Mimetics Sensitize HIV-Infected Cells to MG1-Mediated Death - Molyer Yildirir, Bengisu (Université d'Ottawa | University of Ottawa, 2024)
The main challenge in finding an HIV cure is the targeting and elimination of the HIV reservoir of latently infected CD4+ T-cells and persistently infected macrophages. While these cells are phenotypically indistinguishable from their healthy counterparts, they display impairments in their interferon (IFN) signaling. This makes them susceptible to killing by the interferon sensitive oncolytic rhabdovirus virus MG1. Although MG1 has affinity for latently/persistently HIV-infected cells, its effectiveness and selectivity can be enhanced. To enhance killing, MG1 was combined with the pro-apoptotic molecules, second mitochondria derived activator of caspases (SMAC) mimetic (AEG 40730, LCL-161, birinapant) to kill the latently HIV-infected lymphocytic cell line J1.1 and myelocytic cell line OM10.1. In HIV-infected cell lines, it was shown that the order of administration of MG1 and SMAC mimetics is important to optimize killing. Moreover, increased caspase-3/7 and caspase-1 expression followed cell death, and cell death could not be blocked by the pan-caspase inhibitor ZVAD-fmk or the necroptosis inhibitor necrostatin1-s, alone or in combination, indicating that cell death does not occur via a single pathway. SMAC mimetics have shown to activate the non-canonical NFκB pathway and cause TNFα-dependent or independent death in different models of HIV-infected cells. Here, it was also shown that although there was increased activation of the non-canonical NFκB pathway, this did not result in TNFα production, and no straightforward relationship could be found between TNFα and cell death. In HIV-infected monocyte derived macrophages, there was a significant increase in cell death when MG1 was combined with SMAC mimetics compared to either treatment alone. This increase in cell death was also accompanied by a decrease in proviral HIV DNA. MG1 infection or combination treatment with MG1 and SMAC mimetics resulted in TNFα production, which may be one of the contributors of increased cell death. It was previously shown that VSVΔ51 does not kill latently HIV-infected cells. To see if combination treatment would sensitize cells to VSVΔ51 mediated cell death, OM10.1 cells and HIV-infected macrophages were treated with the combination of VSVΔ51 and SMAC mimetics. This resulted in significantly increased cell death compared to either treatment alone, and was accompanied by a decrease in proviral HIV DNA. To increase MG1’s specificity to target cells of HIV, MG1 plasmids containing full length or modified versions of HIV envelope gp160 were produced. These pseudotyped viral constructs would have restricted tropism and would only be expected to infect the target cells of HIV. Unfortunately, these viral constructs were unable to be rescued and the clones require further optimization. This is the first study to employ combination therapy with oncolytic virus and SMAC mimetics with the goal of eliminating latently HIV-infected cells. These findings that SMAC mimetic treatment and MG1 infection might synergize to specifically kill HIV-infected cells highlights the significant potential of this therapy as an innovative cure approach.
Keywords: HIV; SMAC mimetics; Oncolytic viruses; MG1; VSVΔ51